Evaluation of risk factor and complication of umbilical cord prolapsed in cesarean section - Zahra Rezaee; Mamak Shariat; Mehrnaz Valadan; bita Ebrahim; Bahareh Sedighi; Mehrnoush Kiumarsi; Pouya Bandegi (Mashhad University of Medical Sciences, 2015)
Objectives: Considering the rarity of umbilical cord prolapse (UCP) and lack of accurate data about the risk factors and health outcomes, we aimed to evaluate cases of cesarean section (CS) due to UCP in order to reduce treatment costs and provide information about the mortality and morbidity associated with this condition.Patients & Methods: Of 35,259 cases of CS performed in four hospitals during 2004-2012, 103 cases of UCP were selected as the case group; on the other hand, 318 cases without UCP were classified as the control group. Information was extracted from patients' records and analyzed by SPSS version 18. Results: Prevalence of UCP was estimated at 0.2%. In the case group, the active phase of labor was reported 1.4 times (81% vs 57%-P